Three new Chigger species (Acariformes: Trombiculidae) collected on mammal, bird and reptile from Vietnam - Chau, Nguyen Ngoc (Academia Journal of Biology, 2014)
Three new Chigger species (Acariformes: Trombiculidae) collected on mammal, bird and reptile from Vietnam